Effectiveness of Working Memory Training on Improving Reading Skills in Dyslexic Primary School Students - Farideh Hamidi (آموزش و ارزشیابی, 2016)
In this study, the effectiveness of working memory training on improving reading skills in dyslexic primary school students was investigated. The research design was experimental with pretest-posttest control group .Based on Wechsler test, from among 195 students with dyslexic reading, 60 students were randomly assigned to an experimental and a control group, each with 30 students. In order to examine the reading performance of the participants, the reading and dyslexia test (NOMA) was used. Working memory training was performed for 26 sessions in the experimental group. To analyze the data, the researcher conducted an independent t-test and Mann-Whitney U analysis. The results showed that working memory training based on active memory improved dyslexic students` reading skill. Also, this method increased the skills of dyslexic students in each of the sub-tests